Antibacterial properties of poly (N,N-dimethylaminoethyl methacrylate) obtained at different initiator concentrations in solution polymerization - Dawid Stawski; Karolina Rolińska; Dorota Zielińska; Priyanka Sahariah; Martha Á. Hjálmarsdóttir; Már Másson (Royal Society Open Science, 2022)
The samples of poly(N,N-dimethylaminoethyl methacrylate) were synthesized by radical polymerization. The amount of monomer and solvent was constant as opposed to an amount of initiator which was changing. No clear relationship between polymerization conditions and the molecular weight of the polymer was found, probably due to the branched configuration of produced polymer. Bactericidal interactions in all samples against Gram-positive and Gram-negative bacteria have been demonstrated. However, the observed effect has various intensities, depending on the type of bacteria and the type of sample.